Developing a standard for authenticating halal gelatine catfish skin: A study on the effect of periodization quarantine (istihalah) on gelatin quality in catfish fed with pig-contaminated feeds - Riyanto, Bambang; Wahjuningrum, Dinamella; Ramadhan, Wahyu; Al-Faruqi, Muhammad Umar (Halal Studies and Society, 2024)
The search for sustainable feed alternatives has led to exploring unconventional sources, including food waste, amidst the growing demand for halal gelatin, which has created a significant need for fish skin by-products. Therefore, this study aimed to authenticate the halal status of catfish skin gelatin by verifying feed origin and determining the contents of pig contaminants. Halal standard was verified using a specific DNA analysis of pig components, conducted at each stage, including feed containing pig, fish skin, and catfish gelatin. Gelatin in catfish skin was predominantly composed of amino acids glycine and proline, and fish enlargement stage which led to a skin yield of 5.36 ± 0.75%. Furthermore, the yields of gelatin were 8.67%, 9.94%, and 9.19%, with gel strengths of 133.4 ± 1.2, 129.9 ± 1.4, and 121.9 ± 2.8 bloom, respectively, for the different quarantine periods. The characterization of gelatin using FTIR showed the presence of functional groups, such as amide A, I, II, and III. Real-time PCR detected the presence of pig DNA in feed but not in catfish skin or gelatin. In conclusion, a quarantine period of 0 days for catfish fed pig-containing feed was sufficient to cleanse catfish skin of pig contaminants, with no indication of pig DNA being found.